2009
DOI: 10.1111/j.1439-037x.2008.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Composition, Seedling Emergence and Early Seedling Vigour of Red Kidney Bean Seed Produced at Elevated Temperature and Carbon Dioxide

Abstract: Understanding the influence of growth temperature and carbon dioxide (CO2) on seed quality in terms of seed composition, subsequent seedling emergence and early seedling vigour is important under present and future climates. The objective of this study was to determine the combined effects of elevated temperature and CO2 during seed‐filling of parent plants on seed composition, subsequent seedling emergence and seedling vigour of red kidney bean (Phaseolus vulgaris). Plants of cultivar ‘Montcalm’, were grown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 44 publications
4
32
1
2
Order By: Relevance
“…Thus, crops grown at elevated CO 2 with limiting levels of N will have poorer grain quality. It is also a concern that CO 2 enrichment in the atmosphere during coming decades is likely to produce poor quality grains leading to malnutrition (Thomas et al 2009, Manoj-Kumar et al 2011. Results from our study show a non-significant interaction between CO 2 and temperature, but, in contrary to that Kim and You (2010) reported, a significant decrease in N content of rice plants under combined elevation of CO 2 and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, crops grown at elevated CO 2 with limiting levels of N will have poorer grain quality. It is also a concern that CO 2 enrichment in the atmosphere during coming decades is likely to produce poor quality grains leading to malnutrition (Thomas et al 2009, Manoj-Kumar et al 2011. Results from our study show a non-significant interaction between CO 2 and temperature, but, in contrary to that Kim and You (2010) reported, a significant decrease in N content of rice plants under combined elevation of CO 2 and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, small increases in temperature (2-4°C) may also have more than twice the effect of [CO 2 ] on grain quality, as shown by Williams, Shewry, Lawlor, and Harwood (1995), who noted that starch content, starch grain size and number, and gelatinization were all altered in complex ways with temperature, but with little effect of increased [CO 2 ]. Thomas, Prasad, Boote, and Allen (2009), studying the combined effects of temperature (28/18°C and 34/ 24°C; day/night) and [CO 2 ] (350 and 700 ppm) on the composition of red kidney beans seeds, also found that seed composition was unaffected by elevated [CO 2 ], but seeds produced at 34/24°C showed decreased glucose concentration (44%) and significantly increased concentrations of sucrose (33%) and raffinose (116%) compared to the 28/18°C treatment. These changes may have important consequences for food quality; for example, Sebastian, Kerr, Pearlstein, and Hitz (2000) reported that increases in raffinose amounts create digestive problems in both non-ruminant animals and humans, where the intestinal mucosa does not contain the galactosidase enzyme necessary to digest raffinose.…”
Section: Carbohydratesmentioning
confidence: 97%
“…Other important aspects of seed quality are also maintained at elevated [CO 2 ] in legumes. For example, percent oil in seeds of red kidney bean (Phaseolus vulgaris), peanut (Arachis hypogaea), mung bean (Vigna mungo), and soybean were unaffected by elevated [CO 2 ] (Burkey et al, 2007;Ziska et al, 2007;Thomas et al, 2009). The seed oil composition was altered by elevated [CO 2 ] in some species and experiments, but in general, results do not cause concern for rising [CO 2 ] effects on composition and edible quality of legumes (e.g.…”
Section: Are Leaf and Grain Quality Altered By Growth At Elevated [Comentioning
confidence: 99%